2018
DOI: 10.1007/s00403-018-1830-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased tenascin C and DKK1 in vitiligo: possible role of fibroblasts in acral and non-acral disease

Abstract: Recently, multiple culprits-in addition to melanocytes-have been implicated in the pathogenesis of vitiligo. Among those factors are fibroblasts. However, their exact role has not been clearly elucidated. The aim of the study was to evaluate the possible role played by fibroblasts in vitiligo via studying the expression Tenascin C and DKK1 in acral versus non-acral vitiligo lesions. This case-control study included 19 non-segmental vitiligo patients and ten controls. All patients were subjected to thorough cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…38 Senescence and malfunctioning of the dermal fibroblasts can reduce the secretion of cytokines and growth factors produced by fibroblasts that might result in death of melanocytes and progress of vitiligo. 39,40 The results of the present work also agree with the study done by Wang et al 41 who showed that miRNA-377 negatively regulates SOD1 and SOD2 protein expression, increasing p38MAPK phosphorylation and thioredoxin-interacting protein expression. Furthermore, they stated that the overexpression of miRNA-377 alone enhances oxidative stress in mesangial cells Figure 2 Comparative analysis between localized and generalized vitiligo regarding the expression of studied parameters (data were expressed as mean AE SD, P < 0.05 is statistically significant)…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…38 Senescence and malfunctioning of the dermal fibroblasts can reduce the secretion of cytokines and growth factors produced by fibroblasts that might result in death of melanocytes and progress of vitiligo. 39,40 The results of the present work also agree with the study done by Wang et al 41 who showed that miRNA-377 negatively regulates SOD1 and SOD2 protein expression, increasing p38MAPK phosphorylation and thioredoxin-interacting protein expression. Furthermore, they stated that the overexpression of miRNA-377 alone enhances oxidative stress in mesangial cells Figure 2 Comparative analysis between localized and generalized vitiligo regarding the expression of studied parameters (data were expressed as mean AE SD, P < 0.05 is statistically significant)…”
Section: Discussionsupporting
confidence: 92%
“…These factors influence the growth, pigmentation of melanocytes via the expression of melanin‐producing enzymes, and melanosome transfer 38 . Senescence and malfunctioning of the dermal fibroblasts can reduce the secretion of cytokines and growth factors produced by fibroblasts that might result in death of melanocytes and progress of vitiligo 39,40 …”
Section: Discussionmentioning
confidence: 99%
“…DKK1 might inhibit recruitment of Axin to the plasma membrane, facilitating the phosphorylation of β‐catenin 19 . The expression of DKK1 is highly increased in vitiligo lesions and could play a role in vitiligo by suppression of Wnt signalling 20,21 …”
Section: Possible Molecular Mechanisms Leading To the Downregulation ...mentioning
confidence: 99%
“…19 The expression of DKK1 is highly increased in vitiligo lesions and could play a role in vitiligo by suppression of Wnt signalling. 20,21 Tumour protein P53 (p53) is a negative regulator of the Wnt signalling. 4 The inhibitory effect of p53 on β-catenin is apparently mediated by the ubiquitin-proteasome system.…”
Section: Regulators Of Wnt-βcatenin Signallingmentioning
confidence: 99%
“…TNC acts as an anti-adhesive molecule (108). Since fibroblasts secrete TNC, fibroblasts may malfunction in vitiligo (109) and, therefore, TNC upregulation may impair the adhesion of melanocytes to surrounding keratinocytes and facilitate the process of melanocytorrhagy (109).…”
Section: Tenascin C (Tnc)mentioning
confidence: 99%